The canon of beauty and the use of corticosteroids for aesthetic purposes in Sahrawi refugee camps - Díaz-Meco Niño, Ana María; Calero García, María José; Macías Maroto, Emanuel (Revista Española de Desarrollo y Cooperación, 2024)
Beauty standards in different parts of the world respond to different models. In the Sahrawi refugee camps (CRS), the ideal of women's beauty responds to obesity and white skin. To achieve this, people carry out practices that put their health at risk. The objective of this research is to know what are the substances and practices that Sahrawi women carry out to achieve the predominant beauty standard in their context and what are the repercussions on their health. A descriptive phenomenological qualitative research has been designed in which the information was collected from a total of 70 women (from the provinces of Dakhla and El Aaiún) through individual interviews and focus groups that were audio recorded and transcribed. Discourse analysis was performed. As results, it is highlighted that Sahrawi women, motivated by the standard of beauty in their environment, reported using or knowing women who used bleaching products such as topical corticosteroids, hydrogen peroxide and hydroquinone to lighten the skin, and also antihistamines and oral corticosteroids. to gain weight.
Keywords: Sahrawi refugee camps; women; beauty products; skin whitening products; obesity; drugs